Pharmacological targeting macrophage phenotype via gut-kidney axis ameliorates renal fibrosis in mice. (April 2022) - Xie, Yanan; Hu, Xiaofan; Li, Shanglin; Qiu, Yang; Cao, Rui; Xu, Cong; Lu, Chenqi; Wang, Zhimin; Yang, Jun
Abstract: Renal fibrosis is a non-negligible pathological change in chronic kidney disease (CKD). Increasing evidence indicates that macrophage and gut-kidney axis are correlated with CKD. In this study, we manifest that pharmacological modulating macrophage phenotype via gut-kidney axis is conducive to the alleviation of renal fibrosis. Employing wild-type male mice with unilateral ureteral obstruction (UUO), renal fibrosis was dramatically mitigated in mice treated with antibiotics. And antibiotics application restricted the synthesis of intestinal flora metabolite Trimethylamine N-Oxide (TMAO). However, a 1.3% choline diet enhanced fibrosis. Then we further examined macrophage phenotype through the gut-kidney axis. In in vivo and in vitro culture experiments, the mRNA expression of Nos2, Tnf-α, Il-6, and Il-1β increased under TMAO stimulation. Curbing the NLRP3 inflammasome countered TMAO-induced M1 polarization in bone marrow-derived macrophages. This finding demonstrates that NLRP3 plays a critical part in macrophage polarization. Because of the declining M1 polarization trend in the early stage, M2 macrophages undoubtedly decreased in the tissues. Our results revealed that some metabolites could regulate macrophage phenotype, which matters the severity of renal fibrosis. Thus, pharmacological targeting macrophage phenotype via gut-kidney axis may be a different strategy to treat renal fibrosis. Graphical Abstract: ga1 Highlights: ● Pharmacological targeting macrophage phenotype alleviates murine renal fibrosis. ● Pharmacological modulating metabolite-TMAO affects macrophage phenotype. ● The pharmacological effect works through the gut-kidney axis.